Training of Agricultural Scientists in Information Use - Phadnis, S. P.; Shoalb Ahsan, A.; Vijayalakshmi, N. R. (Journal of Information and Knowledge, 1978)
Highlights the complexity of agricultural information. Gives synopsis of the levels of training courses in information use. Presents details of the contents of the course, and briefly outlines the areas of cooperation between India and USA.